NLP POLITENESS STRATEGIES: IDENTIFYING APPLICATIONS IN THE MAILSUITE WEBSITE FOR SECRETARIES - Putri Adelia; Juwita Permatasari, Rita Hartati (Adisam Publisher, 2025)
This research investigates the use of Neuro-Linguistic Programming (NLP) politeness strategies in email templates for secretaries within the MailSuite platform. Through qualitative analysis, key techniques identified include the Meta-Model, Milton Model, reframing, pacing and leading, anchoring, rapport building, and outcome-oriented strategies. Findings reveal that Building Rapport, Pacing and leading and Outcome-Oriented Techniques are the most dominant, present in 100% of templates. While some templates effectively utilize these strategies, others lack the subtlety needed for professionalism. This study emphasizes the importance of enhancing email communication through NLP techniques to foster more respectful and effective professional interactions.